Evaluation of draw solution effectiveness in a forward osmosis process. Issue 29 (20th June 2016) - Al-aibi, Sami; Mahood, Hammed B.; Sharif, Adel O.; Alpay, Esat; Simcoe-Read, Hannah
Abstract: This work investigates the effectiveness of sodium chloride and sucrose binary draw solutions in a forward osmosis pilot plant unit with either deionised or salt water feeds. Specifically, the effects of draw solution concentration on water flux through the membrane, the overall water recovery and the specific energy consumption of the unit are considered. For both feed types, sodium chloride draw solution exhibited a relatively high effectiveness in terms of all the measured performance indicators. Further, improvements in flux and recovery were also achievable with an increase in the sodium chloride (draw solution) concentration. In contrast, a sucrose-based draw solution led to a severe deterioration of the membrane performance that could not be effectively overcome by an increase in the draw solution concentration. This observation was attributed to the relatively large increase in the viscosity of the draw solution with increase in sucrose concentration. Interestingly, in the case of a salt water feed, an increase in the sucrose draw solution concentration led to a relatively small increase in flux and recovery, suggesting some complex but favourable interaction between the salt and sucrose due to the reverse diffusion of the salt into the draw solution.